KEPEMIMPINAN INSTRUKSIONAL KEPALA SEKOLAH DALAM MEMBUDAYAKAN LINGKUNGAN YANG AMAN, NYAMAN DAN INKLUSIF - Adliroh; Ari Teliti Wilarsati; Setianingrum, Ratih; Nurkolis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teaching and Learning Activities (KBM) can take place optimally if the learning environment is able to support students to explore their potential. This is in line with the statement that education must equip students with the ability to think critically and prepare them for the global challenges of the future. The principal of the school/madrasah has a role as a leader who prepares and implements programs in the context of optimal utilization of school resources. Based on the findings of the research of SD N Kalongan 03 in realizing a safe, comfortable and inclusive learning environment, it is carried out with cooperation between teachers and principals through chain briefing efforts. Briefing from the principal to the teacher for classroom mastery so that students can have a good learning environment.